2022
DOI: 10.3389/fimmu.2022.886290
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Autoimmune Myositis

Abstract: The idiopathic inflammatory myopathies (IIM) are rare, heterogeneous systemic autoimmune disorders, characterized by inflammation of skeletal muscle and multi-organ involvement. Studies to identify genetic risk factors and dysregulated gene expression in IIM aim to increase our understanding of disease pathogenesis. Genome-wide association studies have confirmed the HLA region as the most strongly associated region in IIM, with different associations between clinically-defined subgroups. Associated genes are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Genetic studies have been conducted to identify risk factors and dysregulated gene expression in autoimmune myositis, aiming to understand the disease's underlying mechanisms. Genome-wide association studies (GWAS) have confirmed the human leukocyte (HLA) region as strongly associated with autoimmune myositis, with different associations observed among clinical subgroups [27]. Rare genetic variation, such as mitochondrial DNA variation and somatic mutations, have been found to contribute to disease susceptibility in specific autoimmune myositis subtypes and these mutations are thought to contribute to the pathogenesis of the disease [27].…”
Section: Autoimmune Myositismentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic studies have been conducted to identify risk factors and dysregulated gene expression in autoimmune myositis, aiming to understand the disease's underlying mechanisms. Genome-wide association studies (GWAS) have confirmed the human leukocyte (HLA) region as strongly associated with autoimmune myositis, with different associations observed among clinical subgroups [27]. Rare genetic variation, such as mitochondrial DNA variation and somatic mutations, have been found to contribute to disease susceptibility in specific autoimmune myositis subtypes and these mutations are thought to contribute to the pathogenesis of the disease [27].…”
Section: Autoimmune Myositismentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have confirmed the human leukocyte (HLA) region as strongly associated with autoimmune myositis, with different associations observed among clinical subgroups [27]. Rare genetic variation, such as mitochondrial DNA variation and somatic mutations, have been found to contribute to disease susceptibility in specific autoimmune myositis subtypes and these mutations are thought to contribute to the pathogenesis of the disease [27]. Inclusion body myositis Anti cystosolic 5' nucleotidase 1A Weakness in finger flexors and knee extensors Antisynthetase syndrome Anti-Jo 1 (Antihistidyl) Associated with fever, ILD, arthritis, Raynaud's phenomenon and mechanic's hand Anti-PL 7 (Antithreonyl) Anti-PL 12 (Antialanyl) Anti-OJ (Antiisoleucyl) Anti-EJ (Antiglycyl) Anti-KS (Antiasparaginyl) Anti-Zo (phenylalanyl) Anti-Ha (Antityrosyl).…”
Section: Autoimmune Myositismentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this difference has not yet been identified, however, hypotheses suggest that there is a gene dosage effect of genes escaping X-inactivation in 46, XX females when compared to 46, XY males. An increased rate of X chromosome aneuploidies was seen in patients with systemic lupus erythematosus and Sjögren's syndrome with a higher rate of 47, XXY (Klinefelter's syndrome) and 47, XXX [31][32][33]. The frequency of X chromosome aneuploidies was further investigated in genotyping data generated from an immunotype array.…”
Section: Genetic Contributors Of Sibmmentioning
confidence: 99%
“…2 Idiopathic inflammatory myopathy is classified into subtypes such as dermatomyositis, polymyositis, inclusion body myositis, and immune-mediated necrotizing myositis based on clinical and histopathological features, along with the presence of myositis-specific autoantibodies. 3 The precise etiology of IIMs remains complex and not fully elucidated, with current hypotheses considering genetic predisposition, 4,5 autoimmune mechanisms, 6 and environmental factors, 7 resulting in the onset of IIMs. Treatment options for IIMs include high-dose corticosteroids along with various immunosuppressive and immunomodulatory agents.…”
mentioning
confidence: 99%